Productivity driven by Tana river discharge is spatially limited in Kenyan coastal waters. (1st October 2021) - Mutia, Damaris; Carpenter, Stephen; Jacobs, Zoe; Jebri, Fatma; Kamau, Joseph; Kelly, Stephen J.; Kimeli, Amon; Langat, Philip Kibet; Makori, Amina; Nencioli, Francesco; Painter, Stuart C.; Popova, Ekaterina; et al.
Abstract: The Tana River is the longest river system in Kenya ( 1000 km) and contributes 50% of the total river discharge to Kenyan coastal waters. The river discharges significant amounts of nutrients and sediments, reaching 24, 000 tons per day during the rainy season (March–April), into Ungwana Bay (North Kenya Banks). The bay is an important habitat for high-value Panaeid prawn species which sustain important small-scale fisheries, semi-industrial bottom trawl prawn fisheries, and is the livelihood mainstay in the surrounding counties. In this study we analysed >20 years of satellite-derived chlorophyll-a observations (Chl-a, an index of phytoplankton biomass), along with in situ river discharge and rainfall data, to investigate if the Tana River discharge is a major driver of local phytoplankton biomass in Ungwana Bay and for the neighbouring Kenyan shelf. We find that during the rainy inter-monsoon (March–April), a significant positive relationship (r = 0.63, p < 0.0001) exists between river discharge and phytoplankton biomass. There is a clear time-lag between rainfall, river discharge (1-month lag) and local chlorophyll biomass (2-months lag after discharge). Unlike offshore waters which exhibit bi-annual chl-a peaks (0.22 mg m −3 in February, and 0.223 mg m −3 in August/September), Ungwana Bay displays a single peak per annum in July (2.51 mg m −3 ), with indications that river discharge sustains phytoplankton biomass for several months. Satellite-derived observations and Lagrangian tracking simulations indicate that higher Chl-a concentrations remain locally within the bay, rather than influencing the broader open waters of the North Kenya Banks that are mainly impacted by the wider oceanic circulation. Graphical abstract: Image 1 Highlights: Statistically significant positive correlation between Tana River discharge and Chlorophyll-a in Ungwana Bay. No such correlation away from coastal areas. Productivity over outer North Kenya Banks likely driven by oceanic processes (upwelling) rather than Tana discharge.